Effect of Food on the Pharmacokinetics of Rosuvastatin after Administration of a Single Oral Dose in Dogs - Baek, I.-h.; Kwon, K.-i.; Kim, M.-S. (Drug Research, 2013)
Rosuvastatin is a highly effective inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase and is used for the treatment of patients with hyperlipidemia. We examined the effect of food on the pharmacokinetics of rosuvastatin by administering it while fasting and after intake of low-fat and high-fat meals. We administered a single 10-mg oral dose of rosuvastatin while fasting and after intake of a low-fat and high-fat meal in a parallel design. The plasma concentrations of rosuvastatin were measured using liquid chromatography tandem mass spectrometry (LC-MS/MS), and the pharmacokinetics of rosuvastatin was analyzed using both noncompartmental and compartmental models. The values of area under the curve at 24 h (AUC24 h) and peak plasma concentration (Cmax) in fed conditions were significantly lower than the corresponding values in the fasting conditions. In addition, consumption of a high-fat meal significantly delayed the time required to achieve the maximum concentration (Tmax) of rosuvastatin. Both the models sufficiently explained the effect of food on the pharmacokinetics of rosuvastatin and showed that the volume of distribution (Vc) was increased and absorption rate constant (Ka) was decreased in fed dogs. These findings suggest that food intake affects both the rate and extent of absorption of rosuvastatin, and that rosuvastatin should be administered on an empty stomach to avoid food effect.
Keywords: rosuvastatin; food effect; pharmacokinetics; compartmental; absorption